An active mass damper operated by a system consisting of a neural oscillator and PD controller (A design method of a PD controller for vibration mitigation with consideration of acceleration responses of an auxiliary mass) - Junichi HONGU; Daisuke IBA; Morimasa NAKAMURA; Ichiro MORIWAKI (Nihon Kikai Gakkai ronbunshu, 2016)
This paper proposes a design method of a PD controller with consideration of acceleration responses of an auxiliary mass for active mass dampers (AMDs) operated by a combination system of a neural oscillator and position controller. In the former proposed controller, a desired value of the auxiliary mass was calculated by the output of the oscillator synchronized with the structure's vibration response, and the auxiliary mass was operated to the desired value by the position controller, then the resulting motion of the auxiliary mass mitigated the vibration of the structure. This system can easily solve the stroke limitation problem of the AMD by saturating the desired value of the auxiliary mass within the limit, however the ratio of the control force to the mitigation of the structural acceleration, called as cost-performance, is worse than the system designed by the ordinary linear control method. Therefore, the purpose of this paper is the improvement in the cost-performance of the system by reconsidering the design method of position controller's gains. For this purpose, the gains of the position controller are designed with consideration of the acceleration response of the auxiliary mass, that is tried to approach asymptotically to the ideal sine wave. Numerical simulations with several types of earthquakes indicate that the modified controller has better cost-performance when compared with the former controller.